Dynamic modelling of biomass power plant using micro gas turbine. (August 2015) - Barsali, S.; De Marco, A.; Giglioli, R.; Ludovici, G.; Possenti, A.
Abstract: Biomass is becoming a more and more interesting option to replace conventional fossil fuels for heat and power generation. Small plants able to use solid biomass, collected in the plant neighborhoods, are having a growing diffusion: University of Pisa jointly with some local manufactures has designed, built and tested an externally fired micro gas turbine (EFMGT) supplying 70 kW of electricity as well as 200–250 kW of useful heat. The present paper focuses on the development of a dynamic simulator of the plant. A mathematical model was implemented for the physical and chemical behavior of the biomass combustion process, as well as for heat transfer mechanisms and turbine behavior to assess the plant operating variables in both steady state and transient operating conditions. Comparison between model results and data gathered on a test plant shows a good matching (with deviation below 5%) of the main and most critical variables in a wide range of operating conditions which makes the model suitable for synthesize a closed-loop control system able to ensure the highest performances in power production. Highlights: Direct use of solid biomass in small size power generation would be a good option for electricity generation. Using an externally fired micro gas turbine, the authors developed a 70 kW plant which revealed to be a promising solution. A physically based dynamic model has been developed to consider both combustion and heat to power conversion processes. Calibration and testing showed good match with results. Deviation is less than 20 °C in temperatures and 5 kW in power. A controlling system has been developed to properly regulate the plant.